Association of Low Energy Availability and Suppressed Metabolic Status in Korean Male Collegiate Soccer Players: A Pilot Study. Issue 6 (December 2020) - Lee, Sihyung; Kuniko, Moto; Han, Seungah; Oh, Taewoong; Taguchi, Motoko
Low energy availability (EA) can impair physiological function in athletes. The purpose of this study was to investigate EA status, metabolic status, and bone metabolism with biochemical analysis in Korean male soccer players. Twelve male athletes (18–20 years) completed the study. Body composition and bone mineral density were measured using dual energy X-ray absorptiometry (DXA), while VO2 max was determined by an incremental exercise test. Blood samples were taken for bone marker and hormone analyses. Resting energy expenditure (REE) was measured using the Douglas bag method and predicted using the DXA method. Food diaries and heart rates (HR) during training were recorded, and the Profile of Mood States 2 and Eating Attitude Test 26 were completed. Group differences between low EA (LEA <30 kcal/kg FFM/d, n = 5) and high EA (HEA ≥30 kcal/kg FFM/d, n = 7) were evaluated. The mean EA of the all participants was 31.9 ± 9.8 kcal/kg FFM/d with only two participants having an EA above 45 kcal/kg FFM/d. LEA showed suppressed REE (LEA: 26.0 ± 1.7 kcal/kg/d, HEA: 28.8 ± 1.4 kcal/kg/d, p = .011) with a lower REEratio (LEA: 0.91 ± 0.06, HEA: 1.01 ± 0.05, p = .008) as well as a lower insulin-like growth factor 1 (IGF-1) level (LEA: 248.6 ± 51.2 ng/mL, HEA: 318.9 ± 43.4 ng/mL, p = .028) compared to HEA. There were no group differences in bone markers or other hormone levels. Korean male athletes exhibited low EA status with suppressed metabolism, but there was limited evidence on the effect of EA on bone metabolism, endocrine system, and psychological parameters.